Blood pressure and kidney size in term newborns with intrauterine growth restriction - Matsuoka, Oscar Tadashi; Shibao, Simone; Leone, Cléa Rodrigues (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVE: Low birth weight is associated with higher blood pressure in childhood and adulthood. The aim of this study was to investigate the infl uence of intrauterine growth restriction (IUGR) on newborn systolic blood pressure (SBP). DESIGN AND SETTING: Prospective comparative study at Neonatal and Intensive in Clinical Pediatrics Division, Maternity Hospital in Hospital das Clínicas, Faculdade de Medicina da Universidade de São Paulo. METHODS: 35 newborns with IUGR and 35 without IUGR were compared. Healthy term newborns without malformations, with Apgar score at fi fth minute > 6 were included. Birth weight, kidney weight/birth weight ratio, kidney weight (ultrasound scan), plasma renin activity (PRA) and SBP evolution were analyzed during the fi rst month of life (on 1st, 3rd, 7th and 30th days). RESULTS: SBP evolution, kidney weight/birth weight ratio and PRA did not differ between the two groups. In newborns with IUGR, SBP presented positive correlations with birth weight (r = 0.387 p = 0.026) and BMI (r = 0.412 p = 0.017) on the 7th day of life. Positive correlations with birth weight (r = 0.440 p = 0.01) and birth length (r = 0.386 p = 0.026) were also seen on the 30th day. There was an inverse correlation on the 7th day between SBP and kidney weight/ birth weight ratio (r = -0.420 p = 0.014), but this did not persist to the end of the month. CONCLUSIONS: IUGR seems not to have any infl uence on SBP, PRA or kidney weight among term newborns during their fi rst month of life.